Implementasi Model Pembelajaran Kooperatif Conceptual Understanding Procedures (CUPs) Untuk Meningkatkan Hasil Belajar Siswa - Qadariyah, Laylatul; Zainuddin, Zainuddin; Hartini, Sri (Universitas Lambung Mangkurat, 2015)
Something cause the low learning result of students is a models and methods less variation .Learning inovatian become interesting can improved the learning result of student conducted research purpose at describes the effectiveness implementation of conceptual understanding procedures (CUPs) cooperative learning in improving student learning result on the subject of light reflection. Specifically this study purposed to describe: (1) enforceability LPA, (2) social skills, (3) learning result, (4) student response. This research uses a model of action research Kemmis and McTaggart consisting of III cycles. The subject is a student of class VIII-D SMPN 26 Banjarmasin, on the subject of light reflection. Data collection techniques using observations, questionnaires, testing, and documentation. The results showed that (1) the enforceability of the LPA cycle I (good), cycle II (very good), cycle III (very good), (2) social skills of students cycle I (active ), cycle II (active ), and cycle III (very active), (3) student completness of learning result in the classical cycle I arrive with cycle III experience increasing (4) response of students is about cooperative learningÂ CUPs by category is very good. Be concluded that the implementation cooperative learning model CUPs effective improvedÂ learning result of students of class VIII-D SMPN 26 Banjarmasin on the subject of light reflection. Â